Making sense of the puzzle of matter: the idealist challenge and the quasi-kantian response - Сепетий, Дмитро Петрович (My University, 2018)
The article deals with the Berkleyan problem of the conceivability of mind independent physical reality (matter) and the Russellian problem of the intrinsic properties of matter, recently revitalized by such philosophers of mind as David Chalmers, John Foster, and Howard Robinson. Alternative approaches to this problem — pure dispositionalism, dispositionalism with mental anchoring, Berkleyan idealism, panpsychism, quasi-Kantian quidditism — are outlined and discussed. An argument is made for the tenability and preferability of the quidditist view, which holds that besides spatial and dispositional properties, fundamental physical entities have non-mental non-spatial non-dispositional intrinsic properties (quiddities), in which spatial and dispositional properties are ontologically anchored and grounded in the context of the actual laws of nature, and which are unknowable in the sense of the Kantian thing-in-itself’s unknowability.
Keywords: matter; physical; mental; spatial; disposition; intrinsic property